Implementation Of Ultrasonic Sensor And Fuzzy Logic On Safety And Control Drone System (QUADCOPTER) - Arif, Yunifa Miftachul; Faisal, Muhammad; Kurniawan, Fachrul; Misbahudin, Achmad (Proceedings of the International Conference on Green Technology, 2017)
The development of drone users continues to increase, even though the government has issued Regulation of the Minister of Transportation of the Republic of Indonesia Number 90 of 2015 on the drone usage requirements, but it is still necessary to develop a better drone control system to reduce the risk of accidents caused by user negligence. This research is very important because it is related to safety caused by drone control. In addition, it is also necessary as a reference for the development of drone systems that pay attention to the safety of drones, users, others and the environment. If the research is successful, it will be easier to control so it can minimize the loss caused by drone accident. This research begins with building a quad copter control system that can detect objects around it. Where the object interferes with or obstructs the movement of quad copter. Once the Object is detected a method is needed to determine the direction of motion to avoid it. The method used is fuzzy logic, with ultrasonic sensor as its input. From the experimental results and the implementation can be concluded that Quadcopter can meet the purpose to avoid obstacles, from ultrasonic sensor test the consistent distance that can be detected in the sensor is 0 - 460 cm. The overall system test result is 75% successful.